Study on Bayer digestion behaviour of low grade bauxite with high sulphur. (2018) - Zhou, Xuejiao; Chen, Yongli; Yin, Jianguo; Xia, Wentang; Yuan, Xiaoli; Xiang, Xiaoyan
Low grade bauxite with high sulphur is rich in nature but difficult to be applied industrially. Sulphur in bauxite leads to a series of remarkable negative effects in Bayer process. This work is focused on the dissolution behaviour of sulphur, iron and aluminium from a low grade bauxite. The process parameters such as holding time, alkali concentration and temperature were optimised. Scanning electron microscope, X-ray diffraction and X-ray fluorescence spectrometer were used to characterise the morphology, phase and composition of the bauxite and residue. The results indicate that the relative dissolution rate of aluminium can approach to 75%. The increase in iron dissolution rate enhances the sulphur dissolution rate, enlightening us that it is possible to remove sulphur and iron simultaneously by the seed precipitation for high sulphur bauxite. This research is a novel technical support and theory guidelines for utilising the low grade bauxite with high sulphur.